1984
DOI: 10.1093/eurheartj/5.suppl_f.199
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in cardiac hypertrophy in rat and human heart muscle

Abstract: Changes in the cardiac contents of microsomal RNA and poly(A)-containing mRNA have been examined during induction and regression of heart muscle hypertrophy in rat hearts, as well as possible changes in the subcellular distribution and protein-synthetic activity of cardiac mRNA. In addition, cardiac biopsies from patients with mitral valve diseases were evaluated for their mRNA contents. Induction of heart muscle hypertrophy was accompanied by substantial increases in cardiac microsomal RNA (30-60%) and cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Stenosis of aortic valve increases pressure afterload and ventricular wall stress, resulting in pressure overload to the left ventricle. Indeed, the strong association between left ventricular mass and hs-TnT levels is also in line with experimental and clinical works showing the increased production of troponin T in human and rat myocardium during pressure overload [23]. The troponin elevation seen with left ventricular hypertrophy (LVH) may be the result of myocardial ischemia due to a supply/demand mismatch in hypertrophied myocytes [24].…”
Section: Discussionsupporting
confidence: 72%
“…Stenosis of aortic valve increases pressure afterload and ventricular wall stress, resulting in pressure overload to the left ventricle. Indeed, the strong association between left ventricular mass and hs-TnT levels is also in line with experimental and clinical works showing the increased production of troponin T in human and rat myocardium during pressure overload [23]. The troponin elevation seen with left ventricular hypertrophy (LVH) may be the result of myocardial ischemia due to a supply/demand mismatch in hypertrophied myocytes [24].…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with this notion, TG1 ventricles had significant down-regulation of myosin light chain 2 ventricular isoform (MLC2V) (63 Ϯ 19 versus 100 Ϯ 17, P ϭ 0.0116), a down-regulation also observed in tissues from hypertrophic human hearts and in hypertrophic and hypertensive primate and rodent models. [25][26][27][28] SERCA2a, a marker of heart failure 29 -31 was not significantly different in the ventricles or atria of either line. It is apparent from the literature that different patterns of dysregulation for hypertrophic markers characterize specific murine models; importantly, although some markers may not be up-regulated in specific models, an increase in ␣-skeletal actin is always observed.…”
Section: Bi-atrial Enlargement Cardiac Hypertrophy and Dilationmentioning
confidence: 78%
“…in samples taken from human hearts at autopsy or surgery (2)(3)(4) In our present study, we elected to use the fetal lamb as a have been noted. For example, Aukland et al (2) found that the model for congenital pulmonary stenosis and preductal coarctapattern of myosin iight chain isotype expression was altered in tion of the AO by banding the great vessels in vlero.…”
Section: )mentioning
confidence: 99%
“…3. Derived amino acid sequence of the dominant isoform of sheep cardiac TNT compared with other mammalian cardiac TNT amino acid sequences.…”
Section: ------A-------~------------------------180 W I T : ---~---A-mentioning
confidence: 99%